Mechanistic Contributors to Subclinical Hypothyroidism in obesity: Review of Molecular Evidence for Impaired Thyroid Hormone Receptor Affinity and Actions from Rat Studies - Tulp, Orien L; Obidi, O F; Oyesile, T C; Sainvil, Frantz; Branly, Rolando; Sciranka, A; Rizvi, Syed AA; Awan, Aftab; Anderson, Michael; Einstein, George P (Medical Science: Trends and Innovations Vol. 13, 2025)
Obesity and its pathophysiologic sequela have become a burgeoning medical issue not only in Africa but worldwide. Obese and overweight patients may sometimes present with symptoms suggestive of disordered carbohydrate metabolism and thyroidal parameters including hypothyroidism. However, when the usual routine thyroid battery of labs comes back, they may identify markers of insulin resistance but often fail to identify any obvious abnormal findings in their hypothalamic-thyroidal axis. To determine the potential for subclinical thyroidal actions as a contributing factor for hormonal regulation of energy balance and the development of obesity and metabolic syndrome, studies of resting and catecholamine stimulated metabolism, in vivo thyroid hormone half-life, thyroid hormone binding characteristics and weight gain, groups of lean and obese congenic LA/Ntul//-cp rats were offered stock or high energy diets and in vivo and in vitro parameters of thyroid hormone action determined. The obese phenotype demonstrated impaired thermic responses to diet and environment and cold-induced thermoregulation, in association with decreases in plasma T3 but not T4 concentrations. Administration of I-131 T4 and I-131 T3 in the obese phenotype of corpulent rats resulted in clearance rates for T3, but T4 clearance was consistently prolonged by approximately 50% among the obese phenotype. The plasma half-life of T4 was ~50% longer in obese than in lean littermates, while the half-life of T3 was similar in both phenotypes. Measures of nuclear thyroid hormone receptor density were similar in both phenotypes, but receptor affinity for T3 was diminished in the obese phenotype, consistent with impaired thyroidal actions as a contributing factor for subclinical hypothyroidism in the obese phenotype of this strain. In conclusion, the current trends in the increasing prevalence of obese and overweight conditions will in all likelihood become a pressing global priority to identify and more fully characterize at the molecular, tissue and organ system levels of effective resolutions to the critical issues of overweight and obese conditions. A doable solution must be found, as urgency is emerging that signals that a metabolic and global healthcare epidemic is tantamount to a tsunami if left unattended.